2016
DOI: 10.1186/s13054-016-1532-x
|View full text |Cite
|
Sign up to set email alerts
|

National survey and point prevalence study of sedation practice in UK critical care

Abstract: BackgroundThe present study was designed to (1) establish current sedation practice in UK critical care to inform evidence synthesis and potential future primary research and (2) to compare practice reported via a survey with actual practice assessed in a point prevalence study (PPS).MethodsUK adult general critical care units were invited to participate in a survey of current sedation practice, and a representative sample of units was invited to participate in a PPS of sedation practice at the patient level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
(49 reference statements)
10
45
0
Order By: Relevance
“…A definite weakness of this study is a low participant response rate – 37.8%. The response rate in similar studies in other parts of Europe or world was much higher - Richard-Belle et al showed a 91.1% response rate, Reschreiter et al reported a total of 192 responses out of 302 addressed units (63.5%) [ 12 , 13 ]. This phenomenon can be discussed in a variety of ways, as lack of interest, lack of time or work overload, therefore care must be taken in encouraging intensivists in Poland to participate in practice assessment and monitoring in the future in order to improve quality of care over most dependent patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A definite weakness of this study is a low participant response rate – 37.8%. The response rate in similar studies in other parts of Europe or world was much higher - Richard-Belle et al showed a 91.1% response rate, Reschreiter et al reported a total of 192 responses out of 302 addressed units (63.5%) [ 12 , 13 ]. This phenomenon can be discussed in a variety of ways, as lack of interest, lack of time or work overload, therefore care must be taken in encouraging intensivists in Poland to participate in practice assessment and monitoring in the future in order to improve quality of care over most dependent patients.…”
Section: Discussionmentioning
confidence: 98%
“…It must be underlined that we cannot provide information about the actual practices in Poland as this was a study based on a survey and not a point prevalence study. A way of overcoming this issue may be a point prevalence study as performed by Richards-Belle et al [ 12 ] and shall be undertaken in the future by the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey showed that midazolam was the most commonly chosen agent, and this was followed by propofol and dexmedetomidine. Several surveys performed in different countries showed the same preference towards midazolam, especially if it is performed for >24 h (9)(10)(11)(12)(13)(14)(15)(16). Most of these surveys were conducted before the release of the ACCM pain, agitation and delirium (PAD) guideline, which suggests the use of non-benzodiazepine sedatives (5).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these surveys were conducted before the release of the ACCM pain, agitation and delirium (PAD) guideline, which suggests the use of non-benzodiazepine sedatives (5). Indeed, survey studies from the United Kingdom performed from 2006 to 2015 showed an increase in the preference of propofol over midazolam (10,17,18). However, recent surveys conducted by Chawla et al (15) and Kotfis et al (16) from Poland and India, respectively, show that midazolam is still the most chosen sedative agent.…”
Section: Discussionmentioning
confidence: 99%